Tailored Sugar-Mediated Porous Particle Structures for Improved Dispersion of Drug Nanoparticles in Spray-Freeze-Drying - Semba, Kumi; Kadota, Kazunori; Kämäräinen, Tero; Nakayama, Yuzuki; Hatanaka, Yuta; Uchiyama, Hiromasa; Arima-Osonoi, Hiroshi; Sugiyama, Kazumasa; Tozuka, Yuichi (Langmuir, 2024)
We fabricated porous particles incorporating sugars (mannitol, sucrose, or dextran) and fenofibrate nanoparticles (FNPs) by using spray-freeze-drying (SFD). The type of sugar significantly influenced the pore architecture of the resulting SFD particles. Rapid freezing of droplets containing dextran produced ice encapsulation within a dextran matrix, forming porous dextran particles. In the presence of FNPs, the particle size (approximately 4 μm) and pore volume (0.3 cm3/g) of SFD dextran were barely affected. In contrast, SFD particles derived from mannitol and sucrose exhibited denser structures with a lower pore volume than dextran. SFD mannitol incorporating FNPs produced porous structures. FNPs containing surfactant and polymer, which reduced surface tension and increased viscosity, promoted the formation of small droplets with a polymeric structure and porous particles with a relatively sharp size distribution with a median around 5 μm. FNPs were uniformly distributed in SFD dextran, which featured large pore structures, whereas in SFD mannitol, the Raman signal of FNPs was more broadly distributed across the powder samples. Both morphologies contributed to enhancing the FNP dispersibility within a redispersed suspension of SFD particles. FNPs in SFD mannitol and dextran matrices maintained their particle size distribution from before SFD, showing no aggregation upon redispersion. Dextran formed a highly porous network irrespective of the presence of FNPs, whereas mannitol tended to alter the particle attributes upon FNP inclusion. In conclusion, SFD particles derived from dextran and mannitol might help to increase FNP dispersibility by increasing the formation of porous architectures.<br